The Relationship Between Emotion Regulation and Quarter-Life Crisis Among Generation Z Master’s Degree Students - Ervira Febriati; Damajanti Kusuma Dewi; Riza Noviana Khoirunnisa (Poltanesa, 2026)
High academic demands, career pressures, and social expectations among Generation Z master’s students may increase the risk of experiencing a quarter-life crisis. This study aims to analyze the relationship between emotion regulation strategies, namely cognitive reappraisal and expressive suppression, and quarter-life crisis among Generation Z master’s students. A quantitative approach with a correlational design was employed. The participants were 204 master’s students from the Faculty of Education and the Faculty of Psychology, Universitas Negeri Surabaya, selected using proportional stratified sampling. The instruments used were the Quarter-Life Crisis Scale and the Emotion Regulation Questionnaire (ERQ). Data were analyzed using multiple linear regression with SPSS. The results revealed that cognitive reappraisal and expressive suppression simultaneously had a significant relationship with quarter-life crisis. Specifically, cognitive reappraisal was significantly negatively associated with quarter-life crisis, while expressive suppression showed a positive significant association. The contribution of both emotion regulation strategies to quarter-life crisis was 24.4%. These findings indicate that adaptive emotion regulation strategies such as cognitive reappraisal serve as protective factors, whereas expressive suppression may act as a risk factor in increasing quarter-life crisis among Generation Z master’s students.